Polymorphisms in Toll-like receptor genes are associated with vitiligo - Traks, Tanel; Keermann, Maris; Karelson, Maire; Rätsep, Ranno; Reimann, Ene; Silm, Helgi; Vasar, Eero; Kõks, Sulev; Kingo, Külli (Frontiers in Genetics, 2015)
Background: The family of Toll-like receptors (TLRs) are responsible for recognising various molecular patterns associated with pathogens. Their expression is not confined to immune cells and have been detected in skin cells such as keratinocytes and melanocytes. As part of a generated response to pathogens, TLRs are involved in inducing inflammatory mediators to combat these threats. It is therefore not surprising that TLRs have been implicated in inflammatory skin diseases, including atopic dermatitis and psoriasis. Likewise, as key players in autoimmunity, they have been associated with a number of autoimmune diseases. Based on this, the role of TLRs in vitiligo could be suspected, but is yet to be clearly established. Methods: In order to conduct a genetic association analysis, 30 SNPs were selected from TLR1-TLR8 and TLR10 regions to be genotyped in Estonian case-control cohort consisting of 139 vitiligo patients and 307 healthy control individuals. The patients were further analysed in subgroups based on sex, age of onset, occurrence of vitiligo among relatives, extent of depigmented areas, vitiligo progression activity, appearance of Köbner’s phenomenon, existence of halo naevi, and incidence of spontaneous repigmentation. Results: The most notable finding came with SNP rs179020 situated in TLR7 gene, that was associated in entire vitiligo (Padj = 0.0065) and also several subgroup analyses. Other single marker and haplotype analyses pointed to TLR3, TLR4 and TLR10 genes. Conclusions: This study investigated the genetic regions of nine TLR genes in relation to vitiligo susceptibility. The main results were the associations of TLR7 SNPs with vitiligo, while several other associations were obtained from the remaining TLR gene regions. This suggests that in addition to other inflammatory skin diseases, TLRs affect the development of vitiligo, thus making them interesting targets for future research.